THE PROPHETIC ETHICS IN NABI BARU POETRY COMPILATION BY TRIYANTO TRIWIYANTO - Muna Alfadlilah (The Journal Of English Teaching For Young And Adult Learners, 2022)
Literature reflects the social ideology and criticizes the community that violates the Islamic ideology andmoral values. One of literature works is prophetic literature that discusses about daily life. Propheticliterature refers to literature that involves in human history. The development of prophetic literature withreligious pattern has many elements, including the human-God relation and inter-human relation.Prophetic literature also deals with reality, such as socio-cultural judgment and criticisms. The propheticliterature has three matters: ma'ruf (instructing to do the good things, humanization), nahi mungkar(preventing the evil things, liberation), and tukminu billah (having faith in the God, transcendental). Theresearchers used descriptive-qualitative research with Hermeneutics theory of Hans Georg-Gadamer tointerpret the Nabi Baru poetry compilation written by Triyanto Triwikromo, the definition of prophet, andprophetic or the features of a prophet as the ideal spiritual-individual. As the agent of change, propheticliterature has a motivation to return to the prophetic values and to guide the community in to the rightway. This matter needs three united materials to create unity. This research explains the representations ofhumanism, transcendental, and liberal values. The results showed that Nabi Baru poetry compilation bookby Triyanto Triwikromo contained values, such as humanism, liberal, and transcendental values.